2011
DOI: 10.1103/physrevstper.7.020101
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of students’ conceptions of wave propagation: Findings from a conceptual survey in mechanical waves

Abstract: We recently developed a multiple-choice conceptual survey in mechanical waves. The development, evaluation, and demonstration of the use of the survey were reported elsewhere [ A. Tongchai et al. Int. J. Sci. Educ. 31 2437 (2009)]. We administered the survey to 902 students from seven different groups ranging from high school to second year university. As an outcome of that analysis we were able to identify several conceptual models which the students seemed to be using when answering the questions in the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 31 publications
6
35
0
11
Order By: Relevance
“…The second error (7%) was to answer incorrectly (again, consistently) based on the belief that the particle does not oscillate but instead moves along a line (answer combination D, G, F). These findings agree with those reported by Tongchai et al (2011). However, there is a consistency issue that needs to be pointed out.…”
Section: Propagationsupporting
confidence: 44%
See 3 more Smart Citations
“…The second error (7%) was to answer incorrectly (again, consistently) based on the belief that the particle does not oscillate but instead moves along a line (answer combination D, G, F). These findings agree with those reported by Tongchai et al (2011). However, there is a consistency issue that needs to be pointed out.…”
Section: Propagationsupporting
confidence: 44%
“…Analyzing the frequent errors in both questions, we found that the most frequent error for was to believe or assume that the speed of sound waves depends on their frequency. This tendency was pointed out by Tongchai et al (2011), who studied the consistency of students' answers within this subtopic. Upon carrying out a cross analysis of these questions, we found that 31% of the students chose answers that were based on this incorrect assumption (selecting option B for both).…”
Section: Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) Propagation [2,[10][11][12][13][14][15][16][17][18][19][20][21] (2) Superposition [2,10,11,19,[22][23][24] (3) Reflection [24] (4) Standing waves [25] In the article in which they introduce the MWCS, Tongchai et al [1] concentrated mainly on the development of the test and its evaluation, focusing on validity and reliability. The test was administered to 632 Australian students, ranging from high school to second-year university students, and 270 Thai high school students.…”
Section: Previous Research On the Mwcsmentioning
confidence: 99%